Doggy whys? - Prap, Lila, 1955- (New York : NorthSouth, 2011)
Contains a collection of humorous facts and information about dogs, in simple text with illustrations, presented in question and answer format.
Translation of: Pasji zakaji?.
Publisher's Weekly
School Library Journal
Publisher's Weekly, January 2011
School Library Journal, May 2011
3.7
Keywords: Dogs -- Miscellanea -- Juvenile literature; Dogs -- Miscellanea; Dogs -- Miscellanea